(untitled) (Bangladesh Journal of Botany, 2023)
The gut bacteria of snakehead fish (Channa punctata, C. marulius and C. striata) collected from Chinadi beel, Narsingdi, Bangladesh was characterized and formulated their antibiogram profile. The mean richness of intestinal bacteria in C. punctata was significantly higher in comparison to C. marulius and C. striata. A total of 24 isolates under the genus Bacillus, Enterobacter, Citrobacter, Kluyvera, Vibrio, Pseudomonas and Acinetobacter were identified. The strains of Enterobacter and Pseudomonas showed 100% resistance to eight antibiotics. The isolates of C. punctata were found to be resistant to nine antibiotics followed by C. marulius (8) and C. striata (7) indicating a critical condition of Chinadi beel of being polluted by anthropogenic activities. Bangladesh J. Bot. 52(2): 297-306, 2023 (June)